Buku Panduan Menulis Karangan Deskripsi Berbasis go to Your Post pada Siswa Kelas V SD (Penelitian Research and Development di SDN Gerem 1 Cilegon) - Tatuhilaliyah, Tatu; Wahid, Farid Ibnu; Sholihat, Ilmi; Sobri, Sobri (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2023)
Writing skill is the ability to express ideas, opinions or even feelings to others using written media. Writing is still considered the most difficult skill to master. The study aims to develop a descriptive writing guidebook. The research method used is R&D (Research and Development) with the research design of Borg and Gall modified by Sugiyono. The result of the research is the learning media of guide book to write descriptions based on go to your post. Based on the result of the due diligence of media experts, the criteria are feasible with an average value of 79%. The results of the validation by material experts obtained very feasible criteria with an average value of 87,31%. The results of the validation by linguists obtained the appropriate criteria with an average value of 76%. As for the results of the student response questionnaire on the limited trial obtained an average value of 92% with very good criteria. Based on these results, the final product in the form of a guidebook to write a description essay based on go to your post is declare suitable for use in the learning activities of grade 5 elementary school students.